An early-morning flowering trait in rice can enhance grain yield under heat stress field conditions at flowering stage - Ishimaru, Tsutomu; Hlaing, Khin Thandar; Oo, Ye Min; Lwin, Tin Mg; Sasaki, Kazuhiro; Lumanglas, Patrick D.; Simon, Eliza-Vie M.; Myint, Tin Tin; Hairmansis, Aris; Susanto, Untung; Ayyenar, Bharathi; Muthurajan, Raveendran; et al. (Elsevier, 2022)
An early-morning flowering (EMF) trait is supposed to be effective in enhancing grain yield due to mitigation of heat-induced spikelet sterility at flowering in rice. This study evaluated (i) phenotypic differences between a near-isogenic line carrying a QTL for EMF trait (designated as IR64 +qEMF3) and a recurrent parent, IR64, under wide variation in climates and (ii) whether the EMF trait can enhance grain yield under heat stress at flowering. IR64 +qEMF3 had significant earlier flower opening time (FOT) in diverse environmental conditions including temperate, subtropical, and tropical regions. FOT differentially responded to maximum and minimum air temperatures between genotypes. Under non-heat stress temperatures at flowering, IR64 +qEMF3 had similar grain yield to IR64 with minimal changes in yield components. Seven field trials in heat-vulnerable regions of Myanmar for multiple years showed that higher percentage of grain set contributed to the significantly higher grain yield in IR64 +qEMF3 when plants were exposed to daily maximum air temperatures around 36.1 °C or higher. Lower spikelet sterility in IR64 +qEMF3 was attributed to the earlier FOT during cooler early morning hours. This is the first field study that clearly demonstrates the enhancement of grain yield due to EMF trait under diverse heat stress field conditions at flowering.